2018
DOI: 10.1186/s13287-018-1094-8
|View full text |Cite
|
Sign up to set email alerts
|

Recycle the dental fairy’s package: overview of dental pulp stem cells

Abstract: Adult stem cells are excellent cell resource for cell therapy and regenerative medicine. Dental pulp stem cells (DPSCs) have been discovered and well known in various application. Here, we reviewed the history of dental pulp stem cell study and the detail experimental method including isolation, culture, cryopreservation, and the differentiation strategy to different cell lineage. Moreover, we discussed the future potential application of the combination of tissue engineering and of DPSC differentiation. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 88 publications
1
33
0
1
Order By: Relevance
“…The basic tissue engineering procedures consist of appropriate scaffold manufacture, hydrogel matrix support, and patterning design. The combination of these approaches promotes the development of the desired complex, both in tissue structure and function[ 20 , 80 ].…”
Section: Different Types Of Scaffold Formulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic tissue engineering procedures consist of appropriate scaffold manufacture, hydrogel matrix support, and patterning design. The combination of these approaches promotes the development of the desired complex, both in tissue structure and function[ 20 , 80 ].…”
Section: Different Types Of Scaffold Formulationsmentioning
confidence: 99%
“…The therapeutic role of DSCs in combination with various scaffolds has been extensively investigated in restoring tooth damage or loss due to caries, periodontal disease, trauma, or genetic disorders[ 89 ]. The procedure of dentin formation consists of odontoblastic deposition, vascularization, and neuron formation[ 20 ]. Among multiple approaches to promote dentin formation and teeth tissue regeneration, the application of DSCs with a synthetic pre-designed and optimized scaffold is the most accepted technique for tooth regeneration[ 90 ].…”
Section: Tooth Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human dental pulp stem cells (hDPSCs) are a candidate for this purpose. hDPSCs can be easily obtained from primary teeth lost during childhood or wisdom teeth extracted in adulthood [ 1 ]. hDPSCs are multipotent [ 2 , 3 ] and their facile collection supports regenerative medicine [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that different subsets of dental MSCs may be distinguished on the basis of the expression of surface markers 21 and show variable potential to regenerate dental/oral tissues in vitro and in vivo 17 . In contrast to other SC sources representing the gold standard in regenerative medicine, such as the bone marrow-and the adipose tissue-derived MSCs, dental MSCs have been shown to possess functional peculiarities that render them as the cell source of choice for dental TE 22 .…”
Section: Significancementioning
confidence: 99%